Insights into Thermostability of β-glucuronidase (GUS) through molecular dynamics studies - Ibrahim Ali , Noorbatcha; Hamzah, Mohd. Salleh (2012)
Structural and dynamic factors responsible for the themostability of β-glucuronidase (GUS) are analyzed by performing molecular dynamics simulations of human, E. coli, T. maritima and mutated E. coli GUS at 300 K and 353 K. 3D structures of mesophilic and thermophilic GUS enzymes have been constructed using homology modeling, based on the known crystal structure of human GUS enzyme. The flexibility of backbone atoms and amino acid residues, structural compactness, hydrogen bonds and salt bridges are analyzed during the simulation. The ability of the GUS enzymes to maintain their structural compactness and, similar backbone and residue fluctuations at a range of temperatures is found to be crucial in determining the thermostability. The presence of a large number of Glu-Arg salt bridge pairs stabilizes the structures of T. maritima GUS and mutant E. coli GUS at higher temperatures. The thermolabile residues 150-155 were found to have smaller fluctuations in mutated E. coli GUS.